Leuven Chansonnier: Study/studie - Burn, David J. -1974; Bossuyt, Ignace 1947- (Antwerpen Davidsfonds Alamire Foundation, 2017)
In 2014 a small Brussels auction-house sold a lot containing a statue, an illuminated initial, and a song-book to a private art-dealer. The song-book was brought to the Alamire Foundation/KU Leuven Musicology Research Group for further investigation. The book, it turns out, is a previously entirely unknown late fifteenth-century chansonnier, complete and in its original cloth binding. The appearance of a new such source of any kind is extremely rare, and all the more so of one in unaltered form. It is almost a century since the last such discovery. The manuscript was acquired by intervention of the Léon Courtin – Marcelle Bouché Fund, a fund which is administered by the King Baudouin Foundation, and handed over to the Alamire Foundation, International Centre for the Study of Music in the Low Countries, by means of a long-term loan.Both repertoire and physical characteristics date the source to the last quarter of the fifteenth century, and mark the source as a prestigious and personal object for wealthy nobility. The Leuven Chansonnier is thus an extremely important discovery in at least four respects: it deepens knowledge of the ways in which fifteenth-century song was consumed; it deepens knowledge of the circulation of fifteenth-century courtly song; it provides a new witness for known works, including the most popular songs of the time; and it adds no less than twelve new pieces to the fifteenth-century song repertory.
Text in English and Dutch
Keywords: 15th Century (1401-1500); Music history; Song; Manuscript; Leuven (Belgium)